Effects of some ligands on aspects of calcium and magnesium metabolism - Farningham, David A. H. (The University of Edinburgh, 1984)
In biological solutions, such as plasma, a small proportion of the calcium and magnesium present exists as free ions in equilibrium with a larger inactive fraction which is bound to protein or small diffusible ligands. The effects of ligands on the distribution of calcium and magnesium between these physico-chemical states, and their effects on the kinetics of these minerals in intact sheep and horses form the major part of this study. Trisodium ethylene diamine tetraacetate (EDTA), calcium and sodium borogluconate, and disodium ethane-l-hydroxy-1,1-diphosphonate (EHDP), all exogenous ligands of pharmacological and therapeutic interest were studied. Estimation of total calcium and magnesium concentrations presents few problems. However extensive investigations of possible methods of estimating diffusible and ionic calcium and magnesium were necessary, as was the validation of a method of estimating glomerular filtration rate (GFR) in conscious intact sheep. EDTA, largely in confirmation of published studies, caused an almost stoichiometric shift of plasma calcium into the non-ionized diffusible fraction, and resulted in stoichiometric increments in urinary calcium and EDTA. The renal clearance of EDTA was similar to GFR. In vitro, calcium-borogluconate complex formation was demonstrated and synergism observed between borate and gluconate. During calcium borogluconate infusion a small increase in the concentration of ionized plasma calcium was accompanied by a larger increase in the non-ionized diffusible fraction. Administration of sodium borogluconate resulted in decreased total plasma calcium concentration, probably as a result of decreased renal tubular reabsorption of calcium complexes. Calcium infusion was also associated with reduced GFR, acidosis and slight hypomagnesaemia, the implications of which were discussed. EHDP was found to form large non-diffusible calcium and magnesium complexes in vitro. This was due to aggregation of complexes and not protein binding. Infusion of EHDP resulted in increases in non-diffusible ultrafiltrable calcium in plasma and urine. Evidence also indicated that the renal clearance of EHDP was lower than GFR, presumably due to the low renal clearance of large molecules. Additionally, chronic administration of low doses of EHDP to horses caused a calciuresis too great to be attributable to simple filtration of complexes, suggesting a second mode of action. Limited evidence indicated a similar phenomenon in sheep. Since ammonium chloride induced acidosis results in depletion of bone mineral and EHDP reduces calcium turnover in bone, these drugs were studied simultaneously in mice. Both substances caused significant loss of bone potassium (per gm dry weight); acidosis also reduced bone sodium and total bone fat. Since EHDP did not alter the effects of acidosis it seemed unlikely to be of clinical benefit. The potential of other diphosphonates was discussed.
The effects of some ligands on aspects of calcium and magnesium metabolism